Pedagogi Digital Islami: Strategi Inovatif Pembelajaran PAI - Khoirul Amin; Yuni Maisaroh; Jalaludin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the various strategies implemented by Islamic Religious Education (PAI) teachers in addressing the challenges and opportunities of the digital era. Using a qualitative literature review approach, this research examines multiple scholarly sources and academic publications discussing the integration of technology into Islamic education. The findings reveal that PAI teachers play a strategic role in developing adaptive, creative, and value-based teaching models. The use of digital media, e-learning platforms, collaborative tools, and social media enhances students’ engagement and learning motivation. However, technology integration also poses challenges such as value degradation, digital dependency, and low media literacy among students. Therefore, PAI teachers must develop digital pedagogical competencies and balance spiritual values with technological progress. Consequently, PAI learning strategies in the digital age should focus on fostering Islamic character, critical digital literacy, and ethical reasoning aligned with Islamic principles.